Fishes of the Orinoco in the Wild - Viloria, Ángel L. (Anartia, 2021)
We had waited for at least a decade for this work to come to light. I met its author, Ivan Mikolji, in 2010. He seemed to me, above all, a brave and daring scientist, capable of diving in the waters of creeks, rivers and lagoons in southern Venezuela without fearing the sudden electric shocks of the Electrophorus, the painful spurs of the stingrays or the terrible bites of the frenzied piranhas. He came to my office at the Venezuelan Institute of Scientific Research accompanied by a mutual friend, my old classmate, Alfredo Pérez, ichthyologist and then professor of fisheries at the Universidad Nacional Experimental de Los Llanos “Ezequiel Zamora”. Ivan presented me with a series of impressive underwater videos, in which I was able to appreciate for the first time in their natural environment many of the colorful fish from the Venezuelan Amazon that I used to acquire in aquarist stores in western Venezuela when I was a child (often at quirky high and bloated prices). He spoke to me with simplicity and humility about how he achieved such impressive and original shots with unsophisticated underwater video cameras. However, I immediately noticed that this new-found character was not at all, neither a fish amateur nor an ordinary photographer.